1816 and the Resumption of «Ordinary History». Issue 1 (February 2016) - Jones, Rhys
1816 and the Resumption of «Ordinary History»: Writing in his memoirs, Prince Klemens von Metternich depicted the conclusion of the Napoleonic Wars in 1815 as a return to «ordinary history». As the chaos of revolution subsided, political and temporal order was resumed, inaugurating a perception of historical time that Metternich believed would be sparse, uneventful, stable and slow. This article examines the failure of this vision to be realised within the context of the first full year of the post-revolutionary era: 1816. The temporal strategies devised and implemented in the wake of Waterloo and the Congress of Vienna to stabilise the experience of historical time were themselves undermined by the ambiguous, often contested interpretations of what constituted the «ordinary» course of history. Although the geographic scope is transnational, stretching from Piedmont to Barbados, this article focuses primarily on France and America, and the contemporary chronopolitical disputes that saw those societies struggle to comprehend the new historical and temporal realities established by their respective revolutions. The chronopolitical controversies of 1816 were dominated by the belief that history, which was accelerated beyond control during the revolutionary era, could not be stabilised, or rendered «ordinary».